A contrastive analysis of aspect in English and Moroccan Arabic - Boubekri, Abdelhakim; Ech-Charfi, Ahmed (Lingua Posnaniensis, 2023)
This study endeavors to undertake a comparative analysis of aspect in English and Moroccan Arabic, hereafter referred to as MA, adopting a cognitive linguistic approach, with special attention to the categorization of different situation types as proposed by Radden and Dirven (2007). It also aims to highlight the aspect areas that may challenge Moroccan EFL learners when acquiring this English grammatical construction. The study reveals that aspect is treated differently in English and MA. English aspect hinges on the viewing frame adopted. Therefore, the shift from one viewing frame to another results in the change from one situation type to another. By contrast, in MA, the perfective use calls for the adoption of a maximal viewing frame. However, the imperfective use calls for two interpretations: the event can be seen with either a maximal or a restricted viewing frame. In the absence of elements that co-determine the aspect in MA, general context is the only indication of the appropriate interpretation. The differences in the aspectual systems of English and MA may lead to difficulties in language acquisition. MA learners attempting to learn English, and vice versa, may face challenges in learning both the grammatical structure and its associated meanings.